Copper and lanthanum mixed oxides as catalysts for ethanol Guerbet coupling: The role of La3+ on the production of long-chain alcohols - Perrone, Olavo Micali [UNESP]; Siqueira, Marcos Rechi [UNESP]; Metzker, Gustavo [UNESP]; de Oliveira Lisboa, Daniela Correa [UNESP]; Boscolo, Mauricio [UNESP] (Wiley, 2021)
Mixed oxides derived from the calcination of modified hydrotalcites precursors with copper and lanthanum were synthetized by the co-precipitation method and characterized and applied as catalysts for ethanol Guerbet coupling reactions. The oxides obtained were used to convert ethanol into 1-butanol and long-chain alcohols, mostly 1-hexanol. The selectivity for 1-butanol and 1-hexanol reached 62% and 10% for Cu-MgAl(O) at 280°C. The addition of 1 mol% of La3+ (CuLa-MgAl(O)) increased the number of basic sites comparing to Cu-MgAl(O) changing the selectivity for 1-butanol and 1-hexanol reaching 16.70 and 41.7% at 280°C. The addition of lanthanum and consequently the increase on the catalyst basicity was related to the obtainment of long-chain alcohols due to the enolate formation during the aldol condensation of Guerbet coupling.
Keywords: 1-butanol; 1-hexanol; ethanol; Guerbet coupling; lanthanum